A new approach to assess occupational exposure to airborne fungal contamination and mycotoxins of forklift drivers in waste sorting facilities - Viegas, Carla (2016)
The waste management industry is an important employer, and exposure of waste-handling workers to microorganisms is considered an occupational health problem. Besides fungal contamination, it is important to consider the co-occurrence of mycotoxins in this setting. Forklifts with closed cabinet and air conditioner are commonly used in waste industry to transport waste and other products within the facilities, possibly increasing the risk of exposure under certain conditions. The aim of this study was to assess the fungal contamination and mycotoxin levels in filters from the air conditioning system of forklift cabinets, as an indicator to assess occupational exposure of the drivers working in a waste sorting facility. Cytotoxicity was also assessed to understand and characterize the toxicity of the complex mixtures as present in the forklift filters. Aqueous extracts of filters from 11 vehicles were streaked onto 2% malt extract agar (MEA) with chloramphenicol (0.05 g/L) media, and in dichloran glycerol (DG18) agar-based media for morphological identification of the mycobiota. Real-time quantitative PCR amplification of genes from Aspergillus sections Fumigati, Flavi, Circumdati, and Versicolores was also performed. Mycotoxins were analyzed using LC-MS/MS system. Cytotoxicity of filter extracts was analyzed by using a MTT cell culture test. Aspergillus species were found most frequently, namely Aspergillus sections Circumdati (MEA 48%; DG18 41%) and Nigri (MEA 32%; DG18 17.3%). By qPCR, only Aspergillus section Fumigati species were found, but positive results were obtained for all assessed filters. No mycotoxins were detected in aqueous filter extracts, but most extracts were highly cytotoxic (n = 6) or medium cytotoxic (n = 4). Although filter service life and cytotoxicity were not clearly correlated, the results suggest that observing air conditioner filter replacement frequency may be a critical aspect to avoid worker's exposure. Further research is required to check if the environmental conditions as present in the filters could allow the production of mycotoxins and their dissemination in the cabinet during the normal use of the vehicles.